Welfare‐Based Land Conversion Policy in Maqoshid Syariah Perspective - Alex Teguh Prastyo; Moh Indra Bangsawan (Proceeding International Conference Restructuring and Transforming Law, 2023)
Land conversion is a government effort to provide environmental governance. Land conversion is regulated in Law No. 32/2009 on Environmental Protection and Management. Land conversion can have both positive and negative impacts. The conversion of agricultural land to non‐agricultural uses is a very important discussion because it can have an impact on food production and security from an economic perspective. Conversion of agricultural land will also affect environmental issues. This condition can be studied more deeply actually, seen from the perspective of Islamic economics, the conditions of land conversion carried out by the government from agricultural land to settlements and industries without providing new land for farmers to continue to grow crops and make food security, there are elements that are not fulfilled, namely the attitude of justice and maslahat. This perspective will appear as in the current condition that occurs is the conversion of land as much as possible which results in farmers losing their livelihoods and food security decreasing, so in this case the conversion of land carried out has not been able to prioritize the principles of justice and maslahat and in the view of maqoshid sharia is also considered unable to embody and realize welfare. The type of research is Normative legal research. The approach method used in this research uses qualitative methods.